Governing Climate Change - Bulkeley, Harriet, 1972- and Newell, Peter (New York Routledge Taylor & Francis, 2010)
Examines how climate change is governed by an increasingly diverse range of actors, from civil society and market actors to multilateral development banks, donors and cities.
Includes Notes,Bibliography, Illustrations and Index.
Keywords: Climatic Changes--Government Policy -- Climatic Changes--International Cooperation -- Climatic Changes--Economic Aspects